The poet upstairs - Cofer, Judith Ortiz, 1952- (Pinata Books, 2012)
When a poet moves into the apartment above hers, young Juliana asks to meet her and together they write poems of tropical birds and a river that flows to the sea, typing out words that change the world, if only for a while.